Self Management Support of COVID-19 Patients in Field Hospital, Yangsisurat District Mahasarakham Province - จันทะนุย , กาญจนา; พินิจกลาง, ภิรญา; ไลออน, พิศสมัย; ทรงงาม, จันทร์เพ็ญ (Journal of Health Science of Thailand, 2025)
The objectives of this study were to develop model and evaluate self-management support of COVID-19 patients in field hospital in Yangsisurach District, Mahasarakham Province. It was conducted during the period fron May 2021 to March 2022; and the concept of self-management support was applied. Participants in the research were (1) a group that developed the care model: registered nurse and multidisciplinary teams as work in field hospitals, mental health nurses, primary care group registered nurses, representatives of medical organizations, pharmacists, and infection control nurses (33 people), and representatives of COVID-19 patients/relatives, representatives of volunteers in field hospitals (25 people); and (2) COVID-19 patients group during the treatment period, altogether 432 cases. Research process began with the analysis of the problem situation and develop a self-management support model. It was followed by planning, implementation, observation, reflection, problem solving, and evaluating the results. Research tools included (1) question guideline for interview and focus group discussion, (2) Google form, which processing was linked to Line notify, (3) case management record form when found early warning signs, and (4) report form of collapsed incidents. Quantitative data analysis was performed using descriptive statistics: number, mean, percentage. The qualitative data were analyzed using content analysis. The study found that the self-management support model COVID-19 patients was suitable for the context, namely (1) assigned personnel who were mainly responsible for the assessment of newly admitted patients; (2) prepared a Google form assessment which was processed and linked to Line notify (staff group line) to increase response, (3) prepared a set of knowledge in the form of infographic consisting of disease knowledge, daily schedule guidelines in the waiting center, psychosocial care, advice on lung management, medication, detection of abnormal symptoms, waste management, and a video clip on oxygen measurement and vital signs measurement; (4) appointed volunteer patients (village headmen) in field hospitals to be able to transfer knowledge, and (5) provided knowledge through a variety of channels, such as voice over the Line group. From the operation, it was found that patients with stress/depression received counseling and received advice exactly as needed. All cases had increased knowledge on self-management, and self-care behavior was at a high level; and all patients with symptoms requiring surveillance received management according to the care guidelines. Patients who had completed the treatment according to the guidelines were discharged home (99.07%), and 4 patients deteriorated (0.93%). There was no patients with unplanned recurrence.